Diagnostic efficacy of ultrasound-guided core-needle biopsy of peripheral lymph nodes in sarcoidosis - Boussouar, S.; Medjhoul, A.; Bernaudin, J.F.; Tayebjee, O.; Soussan, M.; Uzunhan, Y.; Nunes, H.; Kambouchner, M.; Martin, A.; Valeyre, D.; Brillet, P.Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background Core-needle biopsy guided by ultrasound can be performed for investigating peripheral lymph node (PLN). The aim of this study was to determine the efficacy of this technique in sarcoidosis. Methods Retrospective review of files of all patients in the database of the radiology department of Avicenne university hospital who underwent PLN biopsies guided by ultrasound from January 2008 to June 2011 (n=292). Cases with either granulomas at histology with the procedure or with a final diagnosis of sarcoidosis were included in the study. Results The histological specimens were adequate in 282 out of 292 cases (96%) showing non-caseating granulomas in 22 cases (n=20 patients with a final diagnosis of sarcoidosis and n=2 patients with tuberculosis). After reviewing clinical files of the 282 patient, 22 were confirmed to have sarcoidosis, at initial presentation (n=19) or later during flare-up or relapse (n=3) with only 2 patients having no granuloma on PLN biopsy. PLN were palpable in 18 cases and only detected by 18FFDG-PET/CT showing increased PLN uptake in 4 cases. The sensitivity and specificity of adequate biopsy were 91 and 99% and the positive and negative predictive values were 91 and 99%, respectively Conclusion Core-needle biopsy guided by ultrasound has a high efficacy for evidencing granulomas in sarcoidosis patients with PLN involvement either clinically palpable or in the presence of 18FFDG-PET/CT uptake.